CHEMICALLY MODIFIED KAPOK SAWDUST FOR ADSORPSTION OF METHYL VIOLET DYE FROM 1 Widi Astuti, Triastuti Sulistyaningsih AQUEOUS SOLUTION - Astuti, Widi; Sulistyaningsih, Triastuti (Universitas Negeri Semarang, 2016)
The potential of chemically modified Kapok sawdust for methyl violet adsorption was investigated in a batch adsorption process. Various physicochemical parameters such as pH, contact time and initial dye concentration were studied. The adsorbent was characterized with Fourier transform infrared spectrophotometer, scanning electron microscope and Brunauer, Emmett and Â Teller (BET) analysis. The optimum conditions for methyl violet adsorption were pH 5 and contact time 30 min. Langmuir, Freundlich and Redlich-Peterson isotherm model were used to analyze the equilibrium data. The experimental data fitted well with the Redlich-Peterson model, with the value of constants are 41.001 L g -1 for K R , 0.523 L 0.799 mg -0.799 for a and 0.799 for Î²